Eschatological Visions in Javanese Exegesis: A Study of Sholeh Darat's Tafsir Fayḍ al-Raḥmān - Muchofifah, Zulia; Kamil, Ahmad Zaidanil; Bakar, Abu (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2023)
This study examines the eschatological interpretations in Tafsir Fayḍ al-Raḥmān by Sholeh Darat, a prominent Javanese mufasir of the 19th century. It delves into the nuances of Sholeh Darat's interpretation of Surah al-Baqarah verses 24-25, exploring its method, sources, and style, particularly in the context of the Javanese cultural milieu. The research employs library research and content analysis methods, incorporating a historical approach to understand Sholeh Darat's interpretations within the socio-political and cultural dynamics of his era. The study reveals that Sholeh Darat's interpretations are a blend of traditional Sunni views and Sufistic insights, which he adapts to the Javanese context, thus making Islamic eschatology more accessible to the local populace. His critiques of Mu’tazilah views and the rationalist movement of his time reflect his role in safeguarding Islamic orthodoxy in Java. The study concludes that Sholeh Darat's eschatological interpretations in Tafsir Fayḍ al-Raḥmān significantly impact both the religious understanding and social practices of Javanese Muslims, strengthening their faith and providing a more relatable and comprehensible view of Islamic eschatology.